Formulation, Organoleptic Evaluation, and Acceptability of Various Teas from Underutilized Nutritious Herbs Compared with Marketed Chinese and Yellow Lipton Tea - Elijah Edache Ehoche; Parth Patel; Chijioke Madu; Johnson Adejoh (Borneo Journal of Pharmacy, 2021)
Herbal teas are nutrient, antioxidant, and hydration-rich brews made from herbs and spices and taken for various purposes. The objective of this study was to formulate tea from clove (Syzygium aromaticum), leaves of lemongrass (Cymbopogon citratus), guava (Psidium guajava), and moringa (Moringa oleifera), as well as compared with Chinese and yellow Lipton Tea. The samples were analyzed for comparative sensory analysis using the 7 points hedonic scale. The sensory evaluation result demonstrated that the color of the clove tea sample (5.87) was most acceptable by participants, while the lemongrass tea (4.46) sample was least acceptable amongst all the tea samples. The clove remained the most accepted tea for aroma (6.07), taste (5.92), texture (5.76), general appearance (5.74), and general acceptability (5.93), in 7 points hedonic scale. However, all tea samples were had significant acceptable scores above average (p <0.05). Owing to the above results, these herbs can be successfully used to produce tea of relatively good quality to encourage herbs' local consumption and stay healthy.